DOZ047.112: Myocardial strain in vascular anomalies with severe tracheomalacia: preliminary results. (24th June 2019) - Massolo, A C; Savignoni, F; Monaco, F; Giliberti, P; Campanale, M; Toscano, A; Pasquini, L; Dotta, A; Bagolan, P; Braguglia, A
Abstract: Background: Vascular anomalies (VA) may cause severe tracheomalacia in some cases. Chronic upper airway obstruction (UAO) is the most common symptom. Increased pulmonary pressure and cardiac dysfunction have been described in patients with chronic UAO, but not in infants with VA. Aim: The aim of this study was to evaluate myocardial strain in infants with VA. Method: Demographics characteristics, respiratory symptoms, and the percentage of tracheal obstruction measured on CT were collected. Left and right ventricle (LV, RV) systolic function were measured with speckle tracking longitudinal strain (LS) analysis. Pulmonary artery pressure was evaluated on tricuspid regurgitation (TR) jet and quantified by end-systolic eccentricity index (EI). Conclusion: Of 15 cases, 6 had tracheal obstruction < 50%, 9 > 50%. LS LV and RV was significantly reduced in cases with obstruction > 50% compared to those with < 50% (LV −15.9% vs −19.9%; RV −15.7% vs −20.5%, respectively) and respiratory symptoms were significantly more pronounced in cases with obstruction > 50%. There are no significant data for TR and EI. Results: In cases with VA with severe tracheomalacia RV and LV myocardial strain is reduced, suggesting myocardial impairment. Further studies with larger sample size are needed to confirm these data and investigate cardiac function. Association with lung function test may be investigated too.